Halal Tourism Development Analysis in Lombok Island - Taqwiem, Ahsani; Al Rasyid Muhammad, Harun; Maulidi , Ali (KnE Social Sciences, 2020)
The enormous economic potential of halal tourism has recently begun to be discussed. Crescent Rating data notes that in 2014 Muslims spend about USD126.1 billion globally on Islamic tourism, and Indonesia as the 6th most popular halal tourism site in the world. This potential needs to be cultivated by Indonesia. Lombok Island as one of the most popular Islamic tourism destinations in Indonesia - in 2015 it received two awards (the Best World Halal Tourism Destination and World Best Halal Honeymoon Destination). The governor of Nusa Tenggara Barat Zuelkiflimansyah has expressed interest in further developing halal tourism in Lombok by promoting some additional destinations such as Senggigi Beach, Gili Trawangan, and Rinjani Mountain. This paper offers SWOT analysis of the development of halal tourism on the Lombok island. Keywords: Islamic Economy, Halal Tourism, Lombok Island